Efficient plant regeneration from embryogenic cell suspension culture of two deepwater rice (Oryza sativa L.) Varieties (Chittagong University Journal of Biological Sciences, 2013)
Cell suspension cultures were initiated from 28-30 d old scutellar-derived embryogenic calli of two deepwater rice varieties HAJA-1 and HAJA-8 and maintained on R2 liquid medium containing 2 mg l-1 2,4-D. The formation of fine embryogenic cell suspensions and subsequent plant regeneration were dependent on plant genotype and culture media. Variety HAJA-8 was found less viable than the other variety HAJA-1. In general, it was observed that variety HAJA-1 showed better performance compared to variety HAJA-8 to R2 medium for the initiation of embryogenic cell lines and the rate of the cell growth was higher in this variety. Plant regeneration was not obtained from cell suspensions of both varieties when cells were cultured on regeneration media semi-solidified with 0.4% (w/v) agarose. Plant regeneration from cell suspensions of the both varieties were obtained when the agrose concentration of the regeneration media was increased from 0.4 to 1% (w/v). The highest plant regeneration frequencies were obtained from cell suspensions of the varieties HAJA-1 and HAJA-8 (48%) and (42%), respectively, pre-treated with water for 5 h and cultured on MS medium supplemented with 2 mg l-1 BAP+1 mg l-1 Proline. Washing cell suspensions with water for a prolonged period of time (15 h and more) inhibited plant regeneration. DOI: http://dx.doi.org/10.3329/cujbs.v5i1.13374 The Chittagong Univ. J. B. Sci.,Vol. 5(1 &2):91-103, 2010